How do utterance measures predict raters' perceptions of fluency in French as a second language?. (January 2016) - Préfontaine, Yvonne; Kormos, Judit; Johnson, Daniel Ezra
While the research literature on second language (L2) fluency is replete with descriptions of fluency and its influence with regard to English as an additional language, little is known about what fluency features influence judgments of fluency in L2 French. This study reports the results of an investigation that analyzed the relationship between utterance fluency measures and raters' perceptions of L2 fluency in French using mixed-effects modeling. Participants were 40 adult learners of French at varying levels of proficiency, studying in a university immersion context. Speech performances were collected on three different types of narrative tasks. Four utterance fluency measures were extracted from each performance. Eleven untrained judges rated the speech performances and we examined which utterance fluency measures are the best predictors of the scores awarded by the raters. The mean length of runs and articulation rate proved to be the most influential factors in raters' judgments, while the frequency of pauses played a less important role. The length of pauses was positively related to fluency scores, indicating a prominent cross-linguistic variation specific to French. The relative importance of the utterance measures in predicting fluency ratings, however, was found to vary across tasks.